MANIFESTATION OF THE TEACHER’S REFLECTIVE PRACTICE AS EXPERIENTIAL LEARNING AND INVESTIGATION OF ONE’S ACTIONS IN PROFESSIONAL ACTIVITIES - Bubnys, Remigijus; Kairienė, Aida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article deals with the teacher’s reflective practice as manifestation of learning from experience and investigation of one’s actions in professional activities, presenting the results of the quantitative empirical study. The conducted exploratory factor analysis, applying rotation of factor axes by Varimax method enabled to identify significant factors of   the teacher’s reflective practice. Four statistically significant factors were distinguished: investigation of professional and personal activities as a guarantee of accumulation and improvement of professional experience; analysis and refection on personal experience as a factor motivating learning; dissemination of acquired experience in the interaction with school community members as a possibility to learn; learning from the experience as a precondition for success of the learning organization.Research results revealed that teachers understand the importance of learning from experience; however, they are not inclined to conduct a deeper analysis of their practice.